POLA INTERAKSI GENG “KLITIH” DI YOGYAKARTA - Muhammad Reza Achsanu Dwitama; Siany Indria liestyasari; Sigit Pranawa (Universitas Hamzanwadi, 2021)
Klitih/Nglitih comes from the Javanese language, which means looking for activities in your spare time. Meanwhile,